BEAUTIFUL CREATURES - Garcia, Kami, (LITTLE, BROWN AND COMPANY, 2010)
In a small South Carolina town, where it seems little has changed since the Civil War, sixteen-year-old Ethan is powerfully drawn to Lena, a new classmate with whom he shares a psychic connection and whose family hides a dark secret that may be revealed on her sixteenth birthday.